Hepatoprotective, Antioxidant, and Anticancer Effects of the Tragopogon porrifolius Methanolic Extract - Tenkerian, Clara (2015)
Tragopogon porrifolius (Asteraceae), commonly referred to as white salsify, is an edible herb used in Lebanese folk medicine to treat cancer and liver dysfunction. In this study, we investigated the antioxidant activity of Tragopogon porrifolius methanolic extract, both in vitro and in vivo, in addition to its hepatoprotective and anticancer activities. Total phenolic and flavonoid contents were measured and found to be  mg GAE/g and  mg QE/g dry weight, respectively. In vitro antioxidant assays revealed an FRAP value of  µmol Fe2+/g of extract and DPPH IC50 value 15.2 µg/mL. In rats subjected to CCl4-induced hepatotoxicity, significant increase in CAT, SOD, and GST levels was detected. The highest dose of the extract (250 mg/kg) recorded a fold increase of 1.68 for SOD, 2.49 for GST, and 3.2 for CAT. The extract also showed substantial decrease in AST (57%), ALT (56%), and LDH (65%) levels. Additionally, the extract caused a dose-dependent decrease in cell viability and proliferation. In conclusion, the methanolic extract of T. porrifolius displayed a relatively high antioxidant activity both in vitro and in vivo as well as hepatoprotective potential against liver toxicity in rats and anticancer effect on MDA-MB-231 and Caco-2 cells.